Zγ production in vector-boson scattering at next-to-leading order QCD - Francisco Campanario; Matthias Kerner; Dieter Zeppenfeld (Journal of High Energy Physics, 2018)
Abstract Cross sections and differential distributions for Zγ production in association with two jets via vector boson fusion are presented at next-to-leading order in QCD. The leptonic decays of the Z boson with full off-shell effects and spin correlations are taken into account. The uncertainties due to different scale choices and pdf sets are studied. Furthermore, we analyze the effect of including anomalous quartic gauge couplings at NLO QCD.